Performance of Implementing Nurses as a Quality Determining Factor Nursing Services - Yunita, Siti Rusmi; Etlidawati, Etlidawati (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
ABSTRACT Nurse performance as a size in assessment of service quality, the success of a nurse in providing service of course will be greatly influenced by various factors, both those that come from the individual Alone and also from environment surrounding area. In know nurse performance can seen from the perspective of reliability, collaboration, empathy, and responsiveness, because nurse performance is often considered a key factor in determining the quality of nursing services provided to patients. The purpose of this study was to determine whether there was a relationship between the performance of implementing nurses and the quality of nursing services. This research method was a quantitative descriptive study with a cross - sectional approach . The population in this study was 1,913. people. The research sample consisted of 96 respondents. Data analysis used the test spearman rank. The results of this study are partly big Respondent assessed that 71 respondents (74.0%) rated good performance . The quality of service of most respondents was in the very satisfactory category with 57 respondents ( 59.4%). The results of the study showed that there was a significant relationship between nurse performance and service quality with the results of the Spearman Rank Test. that has been done, obtained sign = 0.014 (< 0.05). The conclusion is that there is a significant relationship between the performance of implementing nurses and the quality of nursing services in the surgical inpatient room and in Goeteng Taroenadibrata Purbalingga Regional Hospital